Implementasi Keterbukaan Informasi Publik Pada Kantor Wilayah Kementerian Agama Provinsi Kalimantan Tengah - Hasan Basri; Mambang Mambang (Pencerah Publik, 2019)
This research aims to expand the implementation of public information disclosure assessed still experiencing various obstacles. It was at least indicated by the assessment of the central Kalimantan Provincial Information Committee as stated in the Central Kalimantan Provincial Information Commission DECREE number: 048/KEP/KI Kalteng/2018 dated October 12, 2018, where the regional office of the Ministry of Religious Affairs in central Kalimantan was given a value of 39.3. Research is conducted using a qualitative perspective with a case study method. Data collection is done by interview method and document study. The research was conducted at the Regional office of the provincial religious Ministry of Central Kalimantan. The results of the study showed that the implementation of public information disclosure in the regional office of the provincial religious Ministry of central Kalimantan was executed. Some public information services as regulated in the applicable legislation have been published. However, there are still obstacles encountered in the implementation to make some public information that has not been published. These constraints relate to the contents of the policy and its implementation environment.